HGF and RhoGTPases in Cancer Cell Motility - Lane, Jane; A. Martin, Tracey; G. Jiang, Wen (Current Signal Transduction Therapy, 2011)
Hepatocyte growth factor/scatter factor (HGF/SF) acts as a mitogen, motogen and morphogen as well as an important angiogenic factor. In cancer cells, HGF/SF acts mainly as an inducer of cell migration and invasion with multiple motility signals mediated by the HGF receptor, c-MET. An important component in this signalling chain is the Rho/ROCK pathway, with resultant changes in cytoskeletal arrangement leading to cell motility/migration. This article outlines knowledge of HGF/SF in relation to cancer cell motility from previous reviews and focuses on more recent studies on the effect of HGF/SF in relation to RhoC GTPase and ROCK in breast cancer cells.
Keywords: MDA-MB-231